Tecnologia e Política: a modernização naval na Argentina e Brasil, 1900-1930 - Waldmann Júnior, Ludolf (2018)
This thesis seeks to analyse the process of technological modernization of the Argentine and Brazilian navies between 1900 and 1930. During this period, the rivalry between the two great South American countries was fundamental in their naval modernization policy. Argentina, which until then had no relevant fleet, expanded her naval forces in the late nineteenth century when it was involved in an arms race with Chile. In this process, she changed the regional naval balance, surpassing the Brazilians, who responded by approving new naval programs in 1904 and 1906. Thus, a new regional arms race began, centred on the dreadnoughts and that almost led to the emergence of a war. The naval competition gradually lose momentum after 1910, effectively ending with the outbreak of the World War I. The accelerated technological progress in this conflict quickly made both navies obsolete, which then adopted distinct positions: Argentina remained neutral, while Brazil supported the Allied cause, getting help to prepare its fleet, but unable to update it. In the post-war, despite international pressures for disarmament, the South Americans sought to modernize their navies again, but only the Argentineans were able to do so. Considering this period, our objectives are: 1) to understand the policy of naval acquisitions of the two countries from the perspective of their foreign policy; 2) understand how the decisions of naval modernisation were related to the domestic political dynamics in the two countries, focusing on civil-military relations; 3) analyse the naval decision-making process, identifying internal divergences regarding technological choices as well as the impacts that acquired equipment had on the respective navies. The diplomatic and defence policy of Argentina and Brazil was very marked by the regional dynamics, where a competition between these states was based on a regional balance of power perspective that influenced the decisions of naval modernization. In addition to the influence of foreign policy, the domestic and institutional spheres of these navies also affected the process by which they made their acquisitions. The institutional arrangements and patterns of civil-military relations existing in both these periods influenced the process of naval modernization, especially the time of choice to renew the fleet. Given the relative autonomy of decision-making and little political-institutional interest of the rest of the state and society in participating in the process of elaboration of naval programs in the two countries, modernization policies were largely the result of internal decisions in the navies, where there were significant divergences.